Penerapan Model Pembelajaran Pair Check Dalam Meningkatkan Hasil Belajar IPA - Sutarjo, Sutarjo (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This study aims to determine the improvement of science learning outcomes of students on the material Static Electricity in class IX.2 SMP Negeri 1 Kisaran academc year 2016/2017. The subjects of this study are the students of class IX.2 SMP Negeri 1 Kisaran as many as 34 people. The object of this research is the result of student learning using Pair Check model on Static Electricity material. The research instrument used is multiple choice test and observation. Based on the research results obtained pretest average value of 48.33. After giving the action on cycle I, there were 16 people (47,06%) from 34 students who reached the minimum completeness criterion with an average score of 69,41. In cycle II there are 31 people (91.18%) who reach the minimum mastery criteria with an average value of 85.29. It can be concluded that with the Application of Pair Check Learning Model Can Improve Science Results In Electrical Material Static in Class IX.2 SMP Negeri 1 Kisaran academic year 2016/2017. Keywords: pair check, electricity, static electricity Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar IPA siswa pada materi Listrik Statis di kelas IX.2 SMP Negeri 1 Kisaran Tahun Pelajaran 2016/2017. Subjek penelitian ini adalah siswa kelas IX.2 SMP Negeri 1 Kisaran sebanyak 34 orang. Objek penelitian ini adalah hasil belajar siswa menggunakan model pembelajaran Pair Check pada materi Listrik Statis. Instrumen penelitian yang digunakan adalah tes berbentuk pilihan ganda dan observasi. Berdasarkan hasil penelitian diperoleh nilai rata-rata pretest sebesar 48,33. Setelah pemberian tindakan pada siklus I terdapat 16 orang (47,06%) dari 34 orang siswa yang mencapai Kriteria ketuntasan minimum dengan nilai rata-rata 69,41. Pada siklus II terdapat 31 orang (91,18%) yang mencapai kriteria ketuntasan minimum dengan nilai rata-rata 85,29. Dapat disimpulkam bahwa dengan Penerapan Model Pembelajaran Pair Check Dapat Meningkatkan Hasil Belajar IPA Pada Materi Listrik Statis di Kelas IX.2 SMP Negeri 1 Kisaran Tahun Pelajaran 2016/2017. Kata kunci: pair check, listrik, listrik statis